2016
DOI: 10.1177/0731684416682604
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of Precontraint 1202 S2 based on uniaxial tensile and creep tests

Abstract: The purpose of the paper is the estimation of the polyvinyl chloride – polyester-coated fabric (Precontraint 1202 S2) mechanical properties under uniaxial tensile tests as well as short- and long-time creep tests. The uniaxial tests are the basis of non-linear elastic description while the creep tests are used for the evaluation of the stiffness parameters in time and for the identification of the standard viscoelastic model. The paper also includes a short survey of literature concerning the coated woven fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This approach is sometimes called the piecewise linear model and allows one to conduct the first (very quick but approximated) evaluation of the material behavior in the elastic but non-linear ranges. [45][46][47] The presented study of fabric behavior has been limited to the strain level of 0.05 in the warp and to the strain level of 0.1 in the fill direction. This restriction has been applied due to practical and design reasons, as these elongations correspond to the stress levels and geometrical requirements usually practiced in civil engineering structures.…”
Section: Strength Properties and Piecewise Stiffness Linear Approximationmentioning
confidence: 99%
“…This approach is sometimes called the piecewise linear model and allows one to conduct the first (very quick but approximated) evaluation of the material behavior in the elastic but non-linear ranges. [45][46][47] The presented study of fabric behavior has been limited to the strain level of 0.05 in the warp and to the strain level of 0.1 in the fill direction. This restriction has been applied due to practical and design reasons, as these elongations correspond to the stress levels and geometrical requirements usually practiced in civil engineering structures.…”
Section: Strength Properties and Piecewise Stiffness Linear Approximationmentioning
confidence: 99%
“…The literature concerning the subject of coated woven fabrics is very extensive. Every year new investigations are performed on comprehensive studies on the coated woven fabrics [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Performed investigations have shown that the mechanical parameters of the coated woven fabrics are highly influenced by temperature changes [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The literature concerning the subject of architectural fabrics investigations is very extensive. Performed investigations of the coated woven fabrics have shown that the mechanical parameters are highly influenced by temperature changes [13][14][15]; changes in behaviour under uniaxial, biaxial and creep loadings [16][17][18][19][20][21]; glass threads based and PTFE-coated woven fabrics occur a reduction in the tensile strength resulting under waterlogged [22,23]; prove degradation of the tensile strength exposed to weathering and ageing impacts and cyclic loading [24][25][26][27]; exhibits highly material nonlinearity with identified viscoelastic, viscoplastic behaviour [28][29][30][31][32][33][34]; puncture resistance strength increases with the increase of weight percentage of fibres and initial notch significantly reduce the ultimate strength [35][36][37][38]; the failure strength depends on the stress ratio and off-axial angle [39][40][41][42]. The investigations are also performed on: tearing behaviours and tearing strength propagation mechanisms [41,[43][44][45][46], off-axis tearing properties [47,48], achieving 3D strain surfaces on coated woven fabrics, and refined biaxial test procedures [49,50], modelling multi-scale progressive dam...…”
Section: Introductionmentioning
confidence: 99%